The Effect of Motivational Interviewing on Increasing Physical Activity of Obese Postpartum Mothers : Quasi-experimental one group pre-post test - Dhea Ananda S; Efri Leny Rauf; Yuliandary Yunus; Siskawati Umar (International Journal Of Health Science, 2025)
Postpartum obesity increases the risk of postnatal complications and is often triggered by low physical activity. Fatigue, hormonal changes, and the responsibilities of caring for a baby all contribute to this condition. Motivational Interviewing (MI) is a client-centered counseling technique that aims to awaken intrinsic motivation for adopting healthy behaviors, including increased physical activity during the postpartum period. This study analyzed the effect of MI intervention on the physical activity of obese postpartum mothers. A total of 30 respondents were selected through purposive and convenience sampling based on inclusion criteria and accessibility. Physical activity was measured using the International Physical Activity Questionnaire–Short Form (IPAQ-SF). Before the intervention, 63.3% of respondents were in the low physical activity category, indicating a sedentary lifestyle. After a series of MI sessions, there was a significant increase in physical activity levels to the moderate category. The Wilcoxon signed-rank test showed a p-value of 0.000 (< 0.05), indicating a statistically significant improvement in postpartum mothers’ physical activity following the intervention. This finding highlights the effectiveness of Motivational Interviewing in encouraging behavior change during the critical postpartum period. MI not only promotes increased activity but also empowers mothers to make healthier choices through reflective listening, goal setting, and self-efficacy building. Given the positive outcomes, this strategy is highly recommended for integration into midwifery and maternal health education programs. It can play a pivotal role in preventing long-term complications associated with obesity, such as cardiovascular disease, diabetes, and depression. Further studies are encouraged to evaluate the long-term adherence to physical activity and to examine the potential psychological benefits of MI in the postpartum population.